Pembrolizumab-induced secondary adrenal insufficiency due to adrenocorticotrophic hormone deficiency in a patient with non-small-cell lung carcinoma: a case report - Tatsuhiro Fujimiya; Kanako Azuma; Yuki Togashi; Koji Kuwata; Sakae Unezaki; Hironori Takeuchi (BMC, 2024)
Abstract Background Pembrolizumab can cause immune-related adverse events such as adrenal insufficiency (AI). However, there is no consensus regarding appropriate monitoring of adrenal function during subsequent chemotherapy in patients who have received immune checkpoint inhibitors (ICIs) such as pembrolizumab. Case presentation In this report, we discuss the case of a 60s-year-old male patient with non-small cell lung cancer receiving chemotherapy who developed secondary AI due to adrenocorticotrophic hormone (ACTH) deficiency 8 months after the discontinuation of pembrolizumab, which was 17 months after the initiation of pembrolizumab immunotherapy. After 5 months of chemotherapy, he developed fever and diarrhoea, after which chemotherapy was discontinued. Thereafter, he was hospitalised owing to the development of general fatigue and anorexia. Although cortisol and ACTH levels were not measured during chemotherapy, they were measured before hospitalisation, and secondary AI was suspected. After admission, a detailed endocrine workup was performed, and the patient was diagnosed with secondary AI due to ACTH deficiency. Treatment with hydrocortisone was initiated, which markedly improved his general fatigue and anorexia. The patient showed no evidence of progressive disease 9 months after the discontinuation of pembrolizumab. Conclusions Although rare, the possibility of AI should be considered in patients who have received ICIs when nonspecific symptoms develop during or after subsequent chemotherapy, and measurements of endocrine function (including cortisol and ACTH levels) should be performed.